ANALISIS SEKTOR BASIS TERHADAP PERTUMBUHAN EKONOMI - Wayrohi Meilvidiri (Faculty Of Economics and Business, Musamus University, 2023)
The purpose of this study was to examine the effect of the base sector on economic growth in Merauke Regency from 2010 to 2022. The research data used by researchers is GroSS Regional Domestic Product BusineSS. Fields and Economic Growth for the period 2010-2022. This type of quantitative research with a descriptive approach. The sample in this study is 17 economic sectors. This research uses location quotient, dynamic location quotient, shift share, and Pearson correlation analysis methods.The results show that from the analysis of location quantient and dynamic location quantient, there are four sectors which are basic and prospective sectors, namely: Manufacturing Industry; Provision of Accommodation and Food and Drink; and Information and Communication. Meanwhile, from the shift share analysis, there are six sectors that have fast growth and competitiveneSS and have the potential to improve the regional economy, namely: Electricity and Gas Procurement; Construction; Wholesale and Retail Trade; Car and Motorcycle Repair; Transportation and Warehousing; Provision of Accommodation and Food and Drink; and Information and